Sexual violence against women: nurses’ practice - Rosilene Santos Baptista; Olga Benário Batista de Melo Chaves; Inacia Sátiro Xavier de França; Francisco Stélio de Sousa; Michelly Guedes de Oliveira; Carla Carolina da Silva Leite (Rev Rene)
Objective: to investigate the nurses’ practice regarding sexual violence against women. Methods: quantitative cross-sectional research conducted with 27 nurses in six Primary Care Units from each of the health districts of a city in the countryside of the Northeast Region of Brazil. Data collection took place from October to November 2011 through a questionnaire. Results: among the respondents, 96.3% recognized that it is their role to investigate it; 22.2% of nurses questioned their patients about the violence; 85.1% treated suspected and/or confirmed cases; and 15.8% used some protocol during the service. Only 18.5% felt able to treat cases of sexual violence. Conclusion: there were difficulties for the referral of cases and treatment recommendations. Thus, in-service training and dissemination of educational/informative material are mandatory.